Serving clients with developmental disabilities in clinical practice: utilizing a universal design framework. Issue 4 (4th July 2022) - Eisenbaum, Elaine; Womack, Rachel; Dahl, Kristen; Sheppard-Jones, Kathy; Singleton, Patti; Moseley, Emily; Espinosa Bard, Christina
ABSTRACT: People with intellectual and developmental disabilities (IDD) are an underserved population in the mental health field. People with IDD are less likely to receive mental health services compared to the general population. Additionally, many social workers lack confidence in serving this population. Universal design is an approach that can enhance social workers' ability to serve diverse populations, including clients with IDD. This article provides recommendations for a universal design for learning (UDL) framework for clinical practice. UDL creates a welcoming and accessible approach for people with IDD, and promotes the development of therapeutic alliances and engagement in the therapeutic process.